The Pop Theology of Videogames: Producing and Playing with Religion - de Wildt, Lars (Games and Play, 2023)
Young people in the West are more likely to encounter religion in videogames than in places of worship like churches, mosques or temples. Lars de Wildt interviews developers and players of games such as Assassin's Creed to find out how and why the Pop Theology of Videogames is so appealing to modern audiences. Based on extensive fieldwork, this book argues that developers of videogames and their players engage in a 'Pop Theology' through which laymen reconsider traditional questions of religion by playing with them. Games allow us to play with religious questions and identities in the same way that children play at being a soldier, or choose to 'play house.' This requires a radical rethinking of religious questions as no longer just questions of belief or disbelief; but as truths to be tried on, compared, and discarded at will